Transformasi Pendidikan Perempuan Dari Tradisional Ke Modern di Seberang Kota Jambi - Maisah Maisah (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Women's past Education in Seberang Kota Jambi had several limitation. Women only studied religious education since general education is considered for infidels. Transactional education of women to the modern were caused by several factors and people may lose their trust in the scholars. Development of infrastructure can help women to increase their ability to taste higher education. Then women's education in modern times has changed 180 degrees when and the technology always entails the women career live as well as modern information era since these two issues are recognized as the factors in equalized their job opportunity.